Влияние термообработки на электрофизические свойства CdZnTe-детекторов γ-излучения - Kutniy, V. E.; Kutniy, D. V.; Rybka, A. V.; Abyzov, A. S.; Davydov, L. N.; Nakonechny, D. V.; Shlyakhov, I. N. (PE "Politekhperiodika", Book and Journal Publishers, 2005)
The effect of heat treatment (HT) on the electrophysical properties of γ-ray detectors based on a p-type CdZnTe semiconductor compound was investigated. The optimal HT conditions were determined. It was shown that the application of HT allows for a significant reduction in leakage current and an increase in operating voltage, which contributes to an improvement in the spectrometric characteristics of the detector. Experimental results are presented demonstrating that the change in the detector’s characteristics is largely due to modification of the metal-semiconductor interface rather than changes in the properties of the side surface.